2020
DOI: 10.4314/ahs.v20i2.31
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and visual outcomes of ocular injuries in a low resource country

Abstract: Background: Ocular injury is a major cause of ocular morbidity and unilateral visual impairment and represents a consid- erable public health concern especially in low resource societies. Objective: To evaluate the epidemiology and visual outcomes of ocular injuries in southern Ghana. Methods: A retrospective hospital-based case series was conducted. Information on new cases of ocular injuries were re- trieved and parameters including time between injury occurrence and reporting to the clinic, pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
3
8
0
Order By: Relevance
“…To the to the best of the authors' knowledge, the present study is the first to explore the psychological status of eye injury patients with visual outcomes in the geographical region of Crete, Greece and there are few published studies on this subject worldwide (2,3). Most of the eye injuries occurred among men, as expected in accordance with other studies (3,(12)(13)(14). The study revealed that most of eye injuries (36.7%) occurred among self-employed and private-public sector employees, in contrast with studies where most of eye injuries occurred among manual force workers, mainly occupied in farming activities in rural areas (3,10).…”
Section: Discussionsupporting
confidence: 92%
“…To the to the best of the authors' knowledge, the present study is the first to explore the psychological status of eye injury patients with visual outcomes in the geographical region of Crete, Greece and there are few published studies on this subject worldwide (2,3). Most of the eye injuries occurred among men, as expected in accordance with other studies (3,(12)(13)(14). The study revealed that most of eye injuries (36.7%) occurred among self-employed and private-public sector employees, in contrast with studies where most of eye injuries occurred among manual force workers, mainly occupied in farming activities in rural areas (3,10).…”
Section: Discussionsupporting
confidence: 92%
“…Conversely, the proportion of CGI (64.50–67.34%) was higher than that of OGI (26.53–35.5%) in fireworks-related injuries [ 6 , 12 ]. In cases of ocular trauma derived from common causes, CGI was more frequent than OGI [ 14 , 18 , 19 ] with a few exceptions [ 20 ]. The causes and sites of explosion injuries, positional relationship between the injured and the explosives, differences in national or regional working conditions and living standards, and statistical range of eye injury (i.e., simple eye appendage injury or not) are possible reasons for the observed differences.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding eye structure and function, damage that involves the posterior segment is not easily repaired. Involvement of the retina or choroid was revealed as predictive factor of poor VA in previous reports [5,18,27,36]. Few studies have been conducted on ciliary body detachment (CBD), as most case analyses do not include this observation.…”
Section: Discussionmentioning
confidence: 99%
“…Check for updates the hospital, the management protocol instituted in the hospital [8,9]. Certain occupations, school accidents, domestic accidents and cultural practices have been reported to have direct link with some peculiar ocular injuries in Nigeria [9,10].…”
Section: *Corresponding Author: Olufemi O Oyediran Lecturer Department Of Nursing Science Obafemi Awolowo University Ile-ife Nigeriamentioning
confidence: 99%